CORPORATE UNIVERSITY AS A FORM OF EMPLOYEE TRAINING AND DEVELOPMENT IN AMERICAN COMPANIES - Iryna Lytovchenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article deals with the problem of corporate university as a form of employee training and development in American companies. Corporate training plays a leading role in the successful operation of US companies and is a factor of their competitiveness and efficiency in the marketplace. Corporate university is an advanced form of organizational training which emerged in response to the challenges of the information society and the global economy, increased competition in the market, the failure of the traditional institutions of professional education to meet the needs of the modern economy for highly qualified employees. Modern corporate university is a system of organizational development and personnel training, united with a single concept and methodology, inextricably linked and coordinated with the strategies of the organization. The main functions of the corporate university are training of various levels of company employees, knowledge management, formation of common corporate values, development of corporate culture, promotion of innovation. Since organizations have different needs and development strategies, corporate universities of different companies in the United States differ in purpose, objectives, structural characteristics, methods of instruction. The learning process in the corporate university has andragogical focus and is characterized by extensive use of e-learning technologies.